NEGOSIASI KONTRAK KARENA FORCE MAJEURE AKIBAT PANDEMI COVID-19 DITINJAU DARI KITAB UNDANG-UNDANG HUKUM PERDATA - Carissa Dianputri; Tundjung Herning Sitabuana (Fakultas Hukum Universitas Tarumanagara, 2020)
An agreement is an event in which a party tends to carry out another party on what was agreed upon (performance). In the agreement there is a possibility that the debtor will not be able to carry out his performance. (non-performance of contract). In terms of performing (non-performance of contract), the debtor is obliged to reimburse costs, losses and interest as regulated in Article 1245 of the Code Civil. However, if the debtor's can prove the default is caused by force majeure, the debtor is not obliged to pay any fees. It is not known that the covid-19 pandemic throughout the world Indonesian companies are experiencing financial difficulties so that it is difficult to meet their achievements. In connection with this case, the authors conducted research to find out whether this pandemic was categorized as force majeure, and whether the Covid-19 Pandemic could contract negotiations by parties who were unable to meet their achievements. This type of research is normative legal research, which is descriptive (analysis). Secondary data collected through literature study and interviews. This research is using an analytical qualitative method. The results showed that: 1) The covid-19 pandemic can be categorized as a relative force majeure, it means that the covid-19 pandemic has ended, the debtor is obliged to pay any fees and; 2) with the pandemic 19, contract negotiations can be carried out by parties who are unable to meet their achievements in order to obtain an agreement to suspend debt payments from the other party.